Desempenho produtivo, retorno financeiro e econômico do Tifton 85 irrigado - Medeiros, Elton Pilar (2021)
Tifton 85 (Cynodon spp.), is an excellent forage for the intensification of livestock production in Rio Grande do Sul. However, there are invariably losses in production related to water deficit in periods of drought, so irrigation is an alternative to obtain the maximum productive potential. However, supplementary irrigation of pastures must be an economically viable technique and have maximum efficiency. The objective was to measure the effect of irrigation management on productivity, quality, water use efficiency and economic and financial return of Tifton 85 grass. The experiment was conducted in a pasture area cultivated with Tifton 85, already implanted and established, which is divided into paddocks where the animals perform rotational grazing, located in the municipality of São Francisco de Assis, RS. The experimental design was in randomized blocks, total of four blocks and six treatments, with the irrigation depths being 0%; 25%; 50%; 75%; 100% and 125% based on the reference evapotranspiration (ETo) and with a fixed irrigation shift of 7 days, when the rainfall did not supply the crop demand. Evaluations of biometric parameters of forage mass production (MF), plant height, leaf area index, leaf / stem ratio and crude protein (PB) were carried out. In addition, evaluations were made of the efficiency of water use by plants (USA) and of the financial and economic return. The treatments were subjected to analysis of variance (ANOVA), at the level of 5% probability of error, with the help of the SISVAR® software. After the ANOVA, the regression analysis was performed with the aid of the SigmaPlot® 11.0 software. Irrigation promoted an average increase of 22.95%, 36.95%, 44.24%, 50.18% and 52.24% in the forage mass productivity of Tifton 85 grass for 25, 50, 75 depths , 100 and 125% of ETo respectively for the six cycles evaluated. The efficiency in the use of water, showed an inverse relation to the increase of the irrigation depth. With the highest efficiency of use of the average water in the depth of 25% of the ETo. In the depth of 75% of ETo, the highest levels of crude protein in the plant were obtained, totaling an average increase of 20.22% in relation to the treatment without irrigation. The use of irrigation with different depths influenced the variation in leaf area and plant height positively, as the irrigation depth increased to the maximum technical efficiency in grazing cycles where irrigation was the main source of water for the crop, no affecting the leaf/stem ratio. The financial return and the benefit/cost ratio for all scenarios of average animal weight gain increased with the increase in the applied depth, with the largest irrigation depth (125% ETo) having the best results.